Parenting attitudes in people with obsessive-compulsive disorder and emotional symptoms in their children - Frías, Álvaro, (Colegio Oficial de Psicólogos de Madrid, 2020)
This study sought to delineate distinctive parenting attitudes in people with obsessive-compulsive disorder (OCD), speci- fic emotional symptoms in their children, and the association between them. Forty OCD parents and their children were compared with 37 parents with adjustment disorders and their children by using standardized clinical questionnaires. Children of OCD parents exhibited significantly greater (subclinical) emotional symptoms when compared with children of non-OCD parents. After controlling for parents and childrens depression and anxiety symptoms, OCD parents reported significantly poorer parenting attitudes overall relative to non-OCD parents. The presence of sexual/somatic obsessions in OCD parents predicted anxiety symptom severity among their children, but both relationships were mediated by parental involvement. These findings indicate the importance of addressing and treating the distinctive parenting attitudes among people with OCD and its influence on their childrens emotional symptoms.